Sistem Informasi Pengajuan dan Persetujuan Domain untuk Instansi Pemerintah pada Diskominfo Purwakarta Berbasis Web - Jalaludin, Jalaludin; Zahra, Denada Fatimah; Endahti, Les (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The advancement of information technology has significantly influenced how government agencies perform their duties and responsibilities, with information systems and computer technology becoming the backbone for data management and the provision of accurate information. In this context, it is essential to create systems that facilitate an integrated and efficient process for domain application and approval, The development technique uses the waterfall method, which depicts software development as a series of sequential and linear phases. This web-based system enables users to submit domain applications anytime and anywhere, and it enhances the transparency of the application and approval process through real-time monitoring by applicants. The research results indicate that this web-based domain application and approval information system can improve the efficiency and effectiveness of the domain application process at Diskominfo Purwakarta. With this system, the time required for domain application and approval is significantly reduced, and the accuracy and transparency of the process are increased. Additionally, the system enhances user satisfaction by providing ease of access and real-time process monitoring. The adoption of this system also reduces the workload of administrators by allowing organizational units to input data independently. Evaluation results show that the system is well-received by users and meets the operational needs of Diskominfo Purwakarta.